Meta-genomic analysis of Halobacillus trueperi S61 isolated from the Qarhan Salt Lake. Issue 4 (13th December 2022) - Shen, Shuo; Li, Wei; Wang, Jian; Xu, Ruiting
Abstract: The Qarhan Salt Lake is the second largest salt lake in the world and contains a rich and unique range of extremophiles requiring in-depth exploration. Halophilic microorganisms are promising resources for biotechnology due to their flexibility and survivability. The present study first isolated a novel strain of Halobacillus trueperi S61 from the Qarhan Salt Lake, then whole-genome sequencing and comparative genomics using third-generation PacBio combined with second-generation Illumina technology were performed. The whole genome of H. trueperi S61 identified 57, 549 reads and consists of a complete circular chromosome of 4, 047, 887 bp with 43.86% genetic compound (GC) content and no gaps. A total of 139 non-coding ribonucleic acids (RNA) (including 86 tRNA, 30 rRNA, and 23 sRNA), 16 gene islands with 260, 275 bp, and two prophages (with 82, 682 in length) were predicted. The whole genome of H. trueperi S61 was annotated with 3, 982 protein-coding genes using the Nr, Swissport, KOG, and KEGG databases for 3, 980, 3, 667, 2, 998, and 2, 303 genes. In addition, 561 carbohydrate enzymes and 4, 416 pathogen–host interaction-related genes were identified. The protein function of H. trueperi S61 was focused on biological processes with distribution in gene transcription and amino acids as well as carbohydrate metabolism. The novel strain of H. trueperi S61 isolated from the Qarhan Salt Lake primarily preferred protein biological processes and antibiotic resistance, providing a potential resource for biotechnology. HIGHLIGHTS: The whole genome of Halobacillus trueperi S61 isolated from the Qarhan Salt Lake was identified. The Halobacillus trueperi S61 predicted 3982 nucleotides 3567510 in length and 44.57% GC content. The Halobacillus trueperi S61 summarized basic annotation for 3982 protein-coding genes. The Halobacillus trueperi S61 preferred protein biological processes and antibiotic resistance. Graphical Abstract